An efficient secure Internet of things data storage auditing protocol with adjustable parameter in cloud computing - Meng Liu; Xuan Wang; Chi Yang; Zoe Lin Jiang; Ye Li (International Journal of Distributed Sensor Networks)
Nowadays, an increasing number of cloud users including both individuals and enterprises store their Internet of things data in cloud for benefits like cost saving. However, the cloud storage service is often regarded to be untrusted due to their loss of direct control over the data. Hence, it is necessary to verify the integrity of their data on cloud storage servers via a third party. In real cloud systems, it is very important to improve the performance of the auditing protocol. Hence, the well-designed and cost-effective auditing protocol is expected to meet with the performance requirement while the data size is very large in real cloud systems. In this article, we also propose an auditing protocol based on pairing-based cryptography, which can reduce the computation cost compared to the state-of-the-art third-party auditing protocol. Moreover, we also study how to determine the number of sectors to achieve the optimal performance of our auditing protocol in a case of the same challenged data. And an equation for computing the optimal number of sectors is proposed to further improve the performance of our auditing protocol. Both the mathematical analysis method and experiment results show that our solution is more efficient.